210 Characteristics of hospitals that care for patients with firearm injuries: evidence from the nationwide emergncy department sample. (5th May 2020) - Kaufman, Elinore; Delgado, Kit
Abstract : Statement of Purpose: Firearm injury is a public health crisis in the United States, but little is known about the distribution of firearm injury care among health systems. We examined national estimates of ED visits and hospital admissions to describe the hospitals that care for patients with firearm injuries. This research aims to identify areas of focus for practice improvement and hospital-based violence prevention. Methods: Data was collected from the Nationwide ED Sample (NEDS) for 2016. The NEDS is a 20% stratified sample of all U.S. EDs weighted to provide national estimates. We identified firearm-related injuries using ICD-10 external cause-of-injury codes. We described the distribution of firearm injuries among hospitals and characterized hospitals that treat an average of 2 firearm injuries per week (100/year) according to hospital size, ownership, region, teaching status, urban-rural location, and region. Results: Of the 953 hospitals in the NEDS, 818 hospitals weighted to represent 3, 892 hospitals nationally treated a total of 97, 608 firearm injuries in 2016. The median firearm injuries treated was 8 (interquartile range 3, 19). The 226 hospitals (5.8%) that treated ≥100 firearm injuries cared for 47.4% of all firearm injuries, 69.0% of 26, 812 admissions, 60.3% of 12, 775 severely injured patients, and 58.3% of 7, 626 deaths. Eighty-two percent were Level I or II trauma centers and 91% were metropolitan, teaching hospitals, with 57% located in major urban centers. Forty-six percent were in the South, 37% in the West, 29% in the Midwest, and 8% in the Northeast. Conclusions: Most U.S. hospitals care for firearm injuries, but care is concentrated in a small minority of hospitals, primarily in metropolitan trauma centers in the South and West. Significance and Contributions to Injury and Violence Prevention Science: Hospitals treating substantial numbers of gunshot wound patients may be the most appropriate sites for hospital-based violence intervention programs.